ANALISIS RADIUS PEMUTUS BERAM (CHIP BREAKER) TERHADAP KEKASARAN PERMUKAAN PADA PROSES BUBUT - Agus Hardjito (Universitas Lambung Mangkurat, 2018)
In the cutting process on the tirning machine the shape of chips generatedvaries among long chip (continuous chip) and a dashed chip, chip shape isinfluenced by the geometry of the tool including chip breaker radius appliedcutting tool, and the radius of the breaker chip thought to have an influence onworkpiece surface roughness and tools durabulity. The influence of the radius ofthis chip breaker needs to be analyzed for how it effect the value of the surfaceroughness. The goal of my research is to find the optimal surface roughness isgenerated by certain radius enabling have to be used for guidance for thetoolmaker in turning machine in metal manufakturing. The conclusion from thisstudy is the difference in roughness significant value to the amount of burr givenradius breaker.